2009
DOI: 10.1111/j.1365-2184.2009.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐cycle inhibition and apoptosis induced by curcumin and cisplatin or oxaliplatin in human ovarian carcinoma cells

Abstract: The data suggests that curcumin is an interesting natural compound capable of limiting cell proliferation and possibly increasing clinical impact of platinum drugs, in ovarian cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 37 publications
3
44
2
Order By: Relevance
“…A complex study by Montopoli et al [98] confirmed curcumin cytotoxic activity in ovarian cancer cells and strongly revealed its synergistic action to cisplatin and a third generation platinum derivative drug, oxaliplatin-1R, 2R-diamnocycloexanoxalateplatinum (II) leading to an increase of cisplatin's and oxaliplatin's cytotoxicity in wild type human ovarian cancer cell line and C13 cisplatin-resistant ones when they were combined treated. It was shown that curcumin caused a concentration-and time-dependent inhibition of ovarian cancer cell viability.…”
Section: Studies On Curcumin Alone or With Quercetin And Other Compoumentioning
confidence: 96%
See 2 more Smart Citations
“…A complex study by Montopoli et al [98] confirmed curcumin cytotoxic activity in ovarian cancer cells and strongly revealed its synergistic action to cisplatin and a third generation platinum derivative drug, oxaliplatin-1R, 2R-diamnocycloexanoxalateplatinum (II) leading to an increase of cisplatin's and oxaliplatin's cytotoxicity in wild type human ovarian cancer cell line and C13 cisplatin-resistant ones when they were combined treated. It was shown that curcumin caused a concentration-and time-dependent inhibition of ovarian cancer cell viability.…”
Section: Studies On Curcumin Alone or With Quercetin And Other Compoumentioning
confidence: 96%
“…The IC50 values for curcumin were 14.92 μM; 7.87 μM; 6.36 μM after 24 h, 48 h and 72 h, respectively; for cisplatin were as follows: Compared to single-drug treatment, curcumin combined with cisplatin or oxaliplatin, at concentrations lower than IC50 (0.5 μM for all three), caused the best dose-and time-dependent increases in cellcycle arrest and apoptosis. According to Montopoli et al [98] these results suggested a crucial role for curcumin in alteration of cell-cycle parameters, when combined with platinum drugs. It was clearly indicated that concurrent treatment of curcumin with platinum drugs makes cisplatin-resistant ovarian carcinoma cells more susceptible to the action of the platinum drugs.…”
Section: Studies On Curcumin Alone or With Quercetin And Other Compoumentioning
confidence: 97%
See 1 more Smart Citation
“…Studies of human gingival fibroblasts, lung fibroblasts, hepatic stellate cells, synoviocytes and cell lines from various malignant tumors demonstrated that curcumin inhibits cell proliferation and induces apoptosis (Jiang et al, 1996;Atsumi et al, 2006;Chen et al, 2006;Divya and Pillai, 2006;Jackson et al, 2006;Lin et al, 2009;Montopoli et al, 2009;Smith et al, 2010;Wu et al, 2010;Liu et al, 2011). The mechanisms implicated in curcumin-induced apoptosis appear to be DOI:http://dx.doi.org/10.7314/APJCP.2012.13.1.289 Antifibrotic Effect of Curcumin in TGF-β1-Induced Myofibroblasts from Human Oral Mucosa multifactorial, including effect on the stability of p53, the release of cytochrome c from mitochondria, and the generation of ROS (Strimpakos and Sharma, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that curcumin synergistically enhances the eff ect of platinum drugs such as cisplatin and oxaliplatin on the cell cycle arrest and ameliorates eff ect these drugs on ovarian cancer patients (Montopoli et al 2009). AMP-activated protein kinase (AMPK) regulates the involved cellular processes in cellular energy status (Hardie and Carling 1997).…”
Section: Th E Eff Ect Of C Longa and Curcumin On The Female Reproducmentioning
confidence: 99%